High Performance Liquid Chromatographic Assay for the Simultaneous Determination of Posaconazole and Vincristine in Rat Plasma - Hadeel A. Khalil; Ahmed F. El-Yazbi; Tarek S. Belal; Dalia A. Hamdy (International Journal of Analytical Chemistry)
Purpose. Developing a validated HPLC-DAD method for simultaneous determination of posaconazole (PSZ) and vincristine (VCR) in rat plasma. Methods. PSZ, VCR, and itraconazole (ITZ) were extracted from 200 μL plasma using diethyl ether in the presence of 0.1 M sodium hydroxide solution. The organic layer was evaporated in vacuo and dried residue was reconstituted and injected through HC-C18 (4.6 × 250 mm, 5 μm) column. In the mobile phase, acetonitrile and 0.015 M potassium dihydrogen orthophosphate (30 : 70 to 80 : 20, linear gradient over 7 minutes) pumped at 1.5 mL/min. VCR and PSZ were measured at 220 and 262 nm, respectively. Two Sprague Dawley rats were orally dosed PSZ followed by iv dosing of VCR and serial blood sampling was performed. Results. VCR, PSZ, and ITZ were successfully separated within 11 min. Calibration curves were linear over the range of 50–5000 ng/mL for both drugs. The CV% and % error of the mean were ≤18% and limit of quantitation was 50 ng/mL for both drugs. Rat plasma concentrations of PSZ and VCR were simultaneously measured up to 72 h and their calculated pharmacokinetics parameters were comparable to the literature. Conclusion. The assay was validated as per ICH guidelines and is appropriate for pharmacokinetics drug-drug interaction studies.